Cytotoxic and Anti-proliferative Effects of Ethanol Extract of Marine Sponge Stylissa carteri on Colon Cancer HCT-116 Cell Line - Resti Gradia Dwiwina; Sarah Sabrina; Yuni Susanti Pratiwi; Putri Halleyana; Adrikni Rahman; Muhammad Hasan Bashari (Indonesian Journal of Cancer Chemoprevention, 2023)
Colorectal cancer is one of the most diagnosed cancers in the world. KRAS mutations in colon cancer are being responsible for the progressiveness and resistance of the standard therapeutic available. Marine sponge is one the sources for chemotherapy. Stylissa carteri is a marine sponge that lives in Indonesia and its anti-cancer effects are starting to be explored nowadays. The purpose of this study was to determine the cytotoxicity and anti-proliferative effect of ethanol extract of Stylissa carteri against colon cancer cells with KRAS mutations HCT-116 cells. This was an in vitro study using colon cancer cell line HCT-116 which was tested by 3-[4,5-Dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide (MTT) and trypan blue assay. The trypan blue assay was performed on control and treated cells at 72 h. The MTT assay was performed on cells which were previously incubated with Stylissa carteri extract. Sponge Stylissa carteri was taken from Pramuka island, Taman Nasional Kepulauan Seribu, Jakarta. The IC50 of ethanol extract of Stylissa carteri is 5 μg/mL (R square 0.9550) in HCT-116 cells. The trypan blue assay showed doubling time of incubated cell for 48 h was 26.10 h for control and 39.69 h for treated cells, respectively. Ethanol extract of Stylissa carteri has cytotoxic and anti-proliferative effects in HCT-116 colon cancer cells with KRAS mutation.Keywords: Colon Cancer, HCT-116, KRAS Mutation, Marine Sponge, Stylissa carteri.